Land Ownership In Islamic Perspective As Percieved By The Selected Land Owners Of Coconut Plantations In Malabang, Lanao Del Sur - Diamaoden, Arsalan A; Camama, Marwah M.; Abdulhakim, Haimanah R.; Ramos-Minodar, Wedad U.; Salih, Zahiya B. Hadji (Future Science / FSH-PH Publications, 2021)
Islam is a practical religion where it does not stop at laying down certain principles. As in the case of land ownership, Islam ordained a system which provides people, both individual and social ownership rights are addressed equally. This paper attempts to examine the impact of Islamic principles on the values and practices of some Mёranaw land owners in Malabang, Lanao del Sur. This is also to find out the depth of awareness of the land owners regarding ownership and management from the Islamic perspective. The study aimed to further raise the awareness that Islam is not just a religion which calls for peace, but also aimed to address the needs of humanity with its spiritual, moral, economic and social systems. The researchers used a qualitative research using the narrative approach. Field-based research was undertaken from focused group discussion, ocular visits to the area and personal interviews with the informants, including land owners, descendants, managers, and tenants. The general finding of the research concludes the land owners were aware that private ownership of land and property is not ‘absolute’ right rather it is a form of trusteeship given by God. And, there is a significant correlation between religion and values. Thus, the influence of religion on land ownership and management has a great impact on shaping the beliefs and practices of the land owners which resulted peace within the community.